1999
DOI: 10.1097/00006454-199902000-00009
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of vitamin A supplements in relation to mortality among human immunodeficiency virus-infected and uninfected children in Tanzania

Abstract: Vitamin A deficiency, which is common among children in many developing countries, is particularly severe among HIV-infected children. Our findings indicate that vitamin A supplements, a low cost intervention, reduce mortality of HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 30 publications
4
74
0
4
Order By: Relevance
“…Direct Effect of vitamin supplementation to HIV-infected pregnant womensupplementation to neonates is one alternative that has proven effective in decreasing child mortality (Humphrey et al, 1996;Rahmathullah et al, 2003); however, it is not known whether vitamin A supplementation to HIV-uninfected infants born to HIV-infected mothers could increase their risk of becoming infected. Vitamin A supplementation to HIV-infected infants appears to be safe and effective to decrease mortality (Fawzi et al, 1999), morbidity from diarrhea (Coutsoudis et al, 1995), and growth retardation (Villamor et al, 2002). Supplementation starting at 6 months among children who are not at risk of becoming HIV infected is an important public health intervention to decrease overall mortality and morbidity from measles, severe diarrhea, and possibly malaria (Villamor & Fawzi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Direct Effect of vitamin supplementation to HIV-infected pregnant womensupplementation to neonates is one alternative that has proven effective in decreasing child mortality (Humphrey et al, 1996;Rahmathullah et al, 2003); however, it is not known whether vitamin A supplementation to HIV-uninfected infants born to HIV-infected mothers could increase their risk of becoming infected. Vitamin A supplementation to HIV-infected infants appears to be safe and effective to decrease mortality (Fawzi et al, 1999), morbidity from diarrhea (Coutsoudis et al, 1995), and growth retardation (Villamor et al, 2002). Supplementation starting at 6 months among children who are not at risk of becoming HIV infected is an important public health intervention to decrease overall mortality and morbidity from measles, severe diarrhea, and possibly malaria (Villamor & Fawzi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a decline in serum retinol was observed in both groups. The consequences of the potential prevention of decline in serum retinol would positively impact on morbidity (Dudley, 1997;Fawzi et al , 1999;Lartey et al , 2000) and the efficacy of immunisation (Bhaskaram & Rao, 1997), especially in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that improvement in vitamin A status was more likely to impact on mortality attributed to diarrhoeal disease and measles than on mortality attributed to respiratory infection or malaria 23 . One trial showed that periodic vitamin A supplementation of HIV-positive children could reduce all-cause mortality by as much as 63% 24 . It was also found that HIV-infected infants born to mothers who were given vitamin A in the last trimester had better intestinal mucosal integrity when tested at 1-14 weeks, which was not found in non-infected infants 22 .…”
Section: Discussionmentioning
confidence: 99%